Slope Stability Analysis Slope Stability Analysis of Plan Disposal OPD 69 Using Geostudio 2007 PT. Pamapersada Nusantara, South Kalimantan: Plan Disposal OPD 69 PT. Pamapersada Nusantara, South Kalimantan (Georest, 2022)
PT. Pamapersada Nusantara (PAMA) is an industry operating in the field of coal mining contracting, which has an OPD69 disposal which is used as a disposal area for low grade material or overburden. During the formation of the dump, it often experiences landslides caused by the base disposal and the many weak areas on the mining slopes. Therefore the authors identify the occurrence of avalanches at OPD69 so that the slopes become stable and safe, in overcoming this problem a safety factor analysis is carried out. Using geostudio 2007 software to determine the safety factor value with the Morgenstren-price method as a process for making a disposal plan. Based on the safety factor analysis, it was found that SK > 1.25, using an overall slope of 3°. The formation of OPD69 is recommended to follow the redesign dimensions so as to achieve the stability of the disposal slopes that meet the safety criteria. Sections A, B, C, D, and E, with safe slope conditions with an area of 140.47 Ha can accommodate 38,912.12 bcm volume of overburden material at the disposal plan and after being redesigned the volume has changed to 22,260.10 bcm.